2012
DOI: 10.1111/j.1654-1103.2012.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing networks provide useful functional connectivity for plants in fragmented systems

Abstract: Question To what extent does the movement of animals between fragmented habitat patches provide functional connectivity via endozoochorous seed dispersal? Location The Stockholm archipelago, Sweden. Methods We followed all movements of livestock between islands during one grazing season. After each movement, manure was collected and its seed content assessed through seedling emergence. Seedling data were then compared to vegetation surveys from the grazed islands with regard to functional traits. Results Light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…As an example, the seasonal movements of livestock (transhumance) traditionally occurring since centuries in many Mediterranean countries may have played an important role in the dispersal of aquatic organism in this area even though few existing studies on this topic are dealing with terrestrial plants and animals (e.g. Fischer et al, 1996;Auffret et al, 2012). Moreover, pastoral activity all around the world is not the only human-driven activity which may enhance organism dispersal.…”
Section: Dispersal By Human Activitiesmentioning
confidence: 99%
“…As an example, the seasonal movements of livestock (transhumance) traditionally occurring since centuries in many Mediterranean countries may have played an important role in the dispersal of aquatic organism in this area even though few existing studies on this topic are dealing with terrestrial plants and animals (e.g. Fischer et al, 1996;Auffret et al, 2012). Moreover, pastoral activity all around the world is not the only human-driven activity which may enhance organism dispersal.…”
Section: Dispersal By Human Activitiesmentioning
confidence: 99%
“…At the landscape scale, seeds can be dispersed during the organized movement between pastures either guided along paths or transported longer distances ( Fig. 1d; Wessels et al, 2008;Hogan & Phillips, 2011;Auffret et al, 2012). The direction of such movement and transportation will depend on land ownership or membership of local conservation schemes.…”
Section: Livestock and Wild Herbivoresmentioning
confidence: 99%
“…In addition, large herbivores may act as agents of long‐distance dispersal via epi‐ and endozoochory, which promote the interchange of propagules among local communities (Auffret et al. ). Moreover, several studies have reported that an increase in the disturbance caused by large herbivores has driven biotic homogenization by causing a loss of palatable habitat specialists and the expansion of browse‐tolerant generalists (McKinney and Lockwood ; Rooney et al.…”
Section: Introductionmentioning
confidence: 99%